Hydrogen production from ethanol dry reforming over lanthania-promoted Co/Al2O3 catalyst - Fayaz, F. (International Islamic University Malaysia-IIUM, 2018)
La-promoted and unpromoted 10Co/Al2O3 catalysts were synthesized using wet a impregnation method and evaluated in a quartz fixed-bed reactor at different CO2:C2H5OH ratios of 2.5:1-1:2.5 and a reaction temperature of 973 K under atmospheric pressure. X-ray diffraction measurements detected the presence of Co3O4 and CoAl2O4 phases on the surface of both promoted and unpromoted catalysts. BET surface area of promoted and unpromoted 10Co/Al2O3 catalysts was about 143.09 and 136.04 m2.g-1, respectively. The La promoter facilitated Co3O4 reduction, improved the degree of reduction from 86 to 98 and increased metal dispersion from 9.11 to 16.64. The La-promoted catalyst appeared to be a better catalyst in terms of catalytic activity and product yield regardless of reactant partial pressure. Both C2H5OH and CO2 conversions improved significantly with an increase in CO2 partial pressure from 20 to 50 kPa for both catalysts whilst a decline in catalytic performance was observed with rising C2H5OH partial pressure. La addition improved C2H5OH and CO2 conversions up to about 74.22 and 33.80, respectively. Â© 2018 International Islamic University Malaysia-IIUM.